Quality Analysis of Street Lighting Protocol of Pematang Siantar City - Charla Tri Selda Manik (PT Inovasi Pratama Internasional, 2019)
Public Street Lighting (PJU) is part of the utilities needed by the community. Public road lighting is needed to improve traffic safety, environmental safety and public comfort when driving, especially at night. This study aims to determine the light intensity and level of public street lighting (PJU) in Pematang Siantar City, especially Jalan Sutomo. The condition of Jalan Sutomo, Pematang Siantar City is a one-way street. In calculating the luminance intensity ( lux ) of public street lighting, a digital lux meter is used. The type and power of the lamp used for PJU on Jl. Sutomo Pematang Siantar City is a 60 W LED lamp. The height of the PJU pole on Jl. Sutomo in Pematang Siantar City is 9 meters in average with an arm length of 2 meters. The distance between a row of PJU poles is approximately 50 meters, with a road width of approximately 10 meters. The laying of the PJU on Jalan Sutomo, Pematang Siantar City, is by facing each other on each side of the road using a 1 arm lamp post.